Relationship between Storage Duration and Yolk Index, Albumen Index and Haugh Unit of Padjadjaran Quail Eggs in Peak Production Phase - Octaviano, Safira Marwa Naifa; Sujana, Endang; Garnida, Dani (Jurnal Produksi Ternak Terapan, 2026)
Quail eggs are a highly nutritious source of animal protein at an affordable price. However, their internal quality tends to decline during storage due to physicochemical changes. Padjadjaran Quail is a local variety developed through purification and crossbreeding of brown and black strains of Japanese quail (Coturnix coturnix japonica), possessing good egg production potential and quality. Studies on the internal quality of Padjadjaran Quail Eggs during long-term storage remain limited. Therefore, this study aimed to determine the relationship between storage duration and yolk index, albumen index, and haugh unit of Padjadjaran Quail Eggs. The research was conducted over 60 days at room temperature using 420 Padjadjaran Quail Eggs from hens in peak production phase at the Poultry Production Laboratory, Faculty of Animal Husbandry, Universitas Padjadjaran. The data were analyzed descriptively, followed by correlation and regression tests. Results showed a decrease in average yolk index from 0.44 to 0.11, albumen index from 0.12 to 0.01, and haugh unit from 90.28 to 59.56. A very strong correlation was found between storage duration and each parameter. The regression models obtained were Y = 0.327 – 0.004X (yolk index), Y = 0.108 – 0.002X (albumen index) and Y = 91.698 – 0.536X (HU).Keywords: storage duration, quail eggs, yolk index, albumen index, haugh unit